2013
DOI: 10.1136/bmjopen-2012-002270
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and colorectal cancer recurrence and survival: a cohort study

Abstract: ObjectiveTo examine the association between dietary patterns and colorectal cancer (CRC) survival.DesignCohort study.SettingA familial CRC registry in Newfoundland.Participants529 newly diagnosed CRC patients from Newfoundland. They were recruited from 1999 to 2003 and followed up until April 2010.Outcome measureParticipants reported their dietary intake using a food frequency questionnaire. Dietary patterns were identified with factor analysis. Multivariable Cox proportional hazards models were employed to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 38 publications
0
48
0
1
Order By: Relevance
“…For meat intake, a positive association in previous studies was limited to subgroups that we were not able to examine within EPIC: those with a first-degree relative with CRC (18) (post-diagnostic intake) and those who had meat intakes consistently above the median before and after diagnosis (17) . In observational studies of postdiagnostic dietary patterns, a Western pattern characterised by high intake of red and processed meat was found to be associated with poorer outcomes among CRC survivors (31)(32)(33) . The results for post-diagnostic dietary patterns are not entirely consistent: one study found that the Alternative Healthy Eating Index (A-HEI)-2010 was associated with lower mortality, but found no association for the DASH (Dietary Approaches to Stop Hypertension), Alternate Med Score, 'Western' pattern or 'Prudent' pattern (31) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For meat intake, a positive association in previous studies was limited to subgroups that we were not able to examine within EPIC: those with a first-degree relative with CRC (18) (post-diagnostic intake) and those who had meat intakes consistently above the median before and after diagnosis (17) . In observational studies of postdiagnostic dietary patterns, a Western pattern characterised by high intake of red and processed meat was found to be associated with poorer outcomes among CRC survivors (31)(32)(33) . The results for post-diagnostic dietary patterns are not entirely consistent: one study found that the Alternative Healthy Eating Index (A-HEI)-2010 was associated with lower mortality, but found no association for the DASH (Dietary Approaches to Stop Hypertension), Alternate Med Score, 'Western' pattern or 'Prudent' pattern (31) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the present results, an inverse association was detected between the pre-diagnostic plant product component of the WCRF/AICR score and CRCspecific mortality; however, for the animal products component, results were similarly non-significant (34) . Overall, the interpretation of index components remains complex; in one study, the pre-diagnostic red and processed meat pattern associated with poorer CRC survival included fish as a component (33) , which has previously been associated with lower risk of CRC incidence (35) . It is thought that cancer recurrence can be partly attributed to proliferation of micrometastatic disease that was not removed at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the impact of overall diet on the development of IBD, the correlations between groups of foods and nutrients that define different dietary patterns should be taken into account. 12 In several diseases, especially cancer [13][14][15][16][17][18] [20][21][22] Since no prospective studies are available in UC or CD, we conducted a study in a large European prospective cohort to examine the risk of developing UC and CD associated with adherence to Mediterranean diet score and with a posteriori dietary patterns produced by factor analysis.…”
mentioning
confidence: 99%
“…Several studies have identified dietary patterns to investigate the association of the total diet on CRC risk. While the study designs, methods, participant populations, and derived dietary patterns differ, the three reviews [33][34][35], three case-control [36][37], and two prospective cohort studies [38][39][40] all concluded that meat-based diets are associated with an increased risk of CRC and that plant-based diets, rich in fruit, vegetables, and low in red and processed meat, may reduce CRC risk. These findings are consistent with Tantamango-Bartley et al [41] who found that vegetarian versus non-vegetarian dietary patterns were associated with significantly reduced cancer incidence (HR 0.92, 95% CI 0.85-0.99).…”
Section: Discussionmentioning
confidence: 99%